Development of a novel platform of virus-like particle (VLP) based vaccine against coronavirus 2019 (SARS-CoV-2) by exposing of epitopes: an immunoinformatics approach (2020)
The emergence of a rapidly spreading and highly infectious COVID-19 outbreak by a novel coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has caused a global pandemic with unprecedented, social and economic dimensions. Therefore, the development of effective strategies is urgent to control COVID-19 outbreak. According to the recent investigations, cell entry of coronaviruses relies on binding of the viral spike glycoprotein to the host cellular receptors. Therefore, in the present study aimed to predict immunogenic epitopes in silico by analyzed spike protein. In parallel, by screening the immunogenic SARS-CoV-2 spike derived epitopes provided in the literature, we chose a set of epitopes believed to induce immunogenic response. Next, we provided the selected epitopes from both approaches, we performed immunoinformatic analysis that map identically to antigen regions and have antigenic properties. Finally, by suggesting a screened set of epitopes, we designed a novel virus-like particle (VLP) vaccine, optimized to be produced in plants by using molecular farming biotechnology techniques. We anticipate our assay to be a starting point for guiding experimental efforts toward the development of a vaccine against SARS-CoV-2.